Foreign Banks in Sub-Saharan Africa - Do North-South and South-South Banks Induce Different Effects on Domestic Banks? - Birte Pohl (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
In theory, the presence of foreign banks has spillover and competition effects on domestic banks leading to higher efficiency. Next to foreign banks from industrialized countries (north-south banks), foreign banks from developing countries (south-south banks) are important investors in Sub-Saharan Africa (SSA). South-south banks are either regional investors or are hosted in developing countries beyond SSA. This paper studies the competitive advantages and strategies of north-south as well as regional and non-regional south-south banks from a theoretical perspective. Moreover, the study examines theoretically whether these foreign banks induce different effects on domestic banks. To explore these issues empirically, 80 domestic banks in 17 countries of SSA between 1999 and 2006 are considered. The results show that the presence of north-south and south-south banks positively affects the costs of domestic banks. This suggests that domestic banks invest in the modern practices of foreign banks. Domestic banks' margins are positively related to the presence of north-south and nonregional south-south banks indicating a lack of competitive pressure. In contrast, regional south-south banks have a negative impact on the margins of domestic banks.
Keywords: F21; F23; F36; 330; south-south banks; spillover and competition effects; efficiency